Genetic Determinants of Increased Body Mass Index Partially Mediate the Effect of Elevated Birth Weight on the Increased Risk of Atrial Fibrillation - Chen, Songzan; Xu, Tian; Yang, Fangkun; Wang, Yao; Zhang, Kaijie; Fu, Guosheng; Zhang, Wenbin (Frontiers in Cardiovascular Medicine, 2021)
Background: Although several observational studies have shown an association between birth weight (BW) and atrial fibrillation (AF), controversy remains. In this study, we aimed to explore the role of elevated BW on the etiology of AF. Methods: A two-sample Mendelian randomization (MR) study was designed to infer the causality. The genetic data on the associations of single nucleotide polymorphisms (SNPs) with BW and AF were separately obtained from two large-scale genome-wide association study with up to 321,223 and 1,030,836 individuals respectively. SNPs were identified at a genome-wide significant level (p-value < 5×10-8). The inverse variance-weighted (IVW) method was employed to obtain causal estimates as our primary analysis. Sensitivity analyses with various statistical methods were applied to evaluate the robustness of the results and multivariable MR analysis was conducted to determine whether this association was mediated by body mass index (BMI). Results: In total, 144 SNPs were identified as the genetic instrumental variables. MR analysis revealed a causal effect of elevated BW on AF (OR = 1.27, 95% CI = 1.14-1.40, P = 5.70×10-6). All the results in sensitivity analyses were consistent with the primary result. The effect of BW on AF was attenuated when adjusted for BMI (OR = 1.16, 95% CI = 1.01-1.33, P = 0.04) Conclusions: Our findings indicate a causal effect of BW on AF, which may be partially mediated by BMI.